2001
DOI: 10.2136/sssaj2001.1688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Carbon on Movement of Simazine and 2,4‐D in Soils

Abstract: stimulate soil microbial activity, which could potentially lead to accelerated degradation, reducing the total Organic amendment (OA) addition is an agricultural practice that amount of chemical available for leaching and to injure can greatly affect pesticide behavior in soil. The influence of three OAs, consisting of a liquid amendment (LOA), solid (SOA) humic crops planted in rotation (Felsot and Dzantor, 1995; amendment, and a solid urban waste (SUW), on sorption, persistence,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 42 publications
2
51
0
1
Order By: Relevance
“…Soil amendments like olive mill residues and winery wastes have been shown to influence other soil pesticide processes like leaching and degradation (Cox et al 2001;Thevenot et al 2009). Adding compost to soils was generally shown to decrease herbicide mineralization and to favor the stabilization of herbicide residues (Barriuso et al 1997).…”
Section: Changes In the Transport Properties Versus Collapse Of The Amentioning
confidence: 99%
See 1 more Smart Citation
“…Soil amendments like olive mill residues and winery wastes have been shown to influence other soil pesticide processes like leaching and degradation (Cox et al 2001;Thevenot et al 2009). Adding compost to soils was generally shown to decrease herbicide mineralization and to favor the stabilization of herbicide residues (Barriuso et al 1997).…”
Section: Changes In the Transport Properties Versus Collapse Of The Amentioning
confidence: 99%
“…The term Bbioavailability^refers to the fraction of a chemical in soil that can be taken up by living organisms or the degree to which a compound is free to move to an organism (Stokes et al 2005). The environmental fate of pesticides in soils is influenced by the addition of exogenous carbon (compost, biochar, or activated carbon), thereby increasing the organic matter content of the soil and consequently affecting sorption and transport of many organic pollutants in soils (Barriuso et al 1997;Cox et al 2001;Beesley et al 2010;Huang et al 2013;Marchal et al 2013). Several studies have shown that the addition of exogenous carbon results in a decrease in groundwater contamination by leaching (Sánchez-Camazano et al 1997;Cox et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…4; Table 3), which agrees with the results observed in the sorption and degradation studies (Table 2). Thus, the herbicide-WSOC interaction might be in part responsible for the greater diuron persistence in these amended soils as a consequence of the formation of stable complexes which also protected herbicide molecules from soil microorganisms (Cox et al, 2001).…”
Section: Leaching Studiesmentioning
confidence: 99%
“…Degradation and sorption are key processes affecting the environmental fate and transport of weak acid herbicides in soils (Cox et al 2001;Celis et al 2005;Sørensen et al 2006). Sorption, which controls herbicide concentrations in the soil solution, is often found to limit herbicide degradation in soil by reducing its concentrations in the aqueous solution (Jensen et al 2004;Dyson et al 2002).…”
Section: Introductionmentioning
confidence: 99%